Volcanic reservoirs in petroleum exploration - Zou, Caineng, 1963- (Elsevier, 2013)
As the world faces ever-increasing energy demands, we must look to new sources of oil and gas in addition to alternative energy sources. Volcanic reservoirs are one such new source and thus an important exploration area and a hot topic in petroleum exploration. There are issues unique to dealing with volcanic reservoirs, and scientists need to understand the differences between volcanic reservoirs and other major reservoir types to move forward with petroleum exploration and production in these basins.
Keywords: Hydrocarbon reservoirs.; Volcanic soils.; Petroleum -- Geology -- China.; China.; elektronické knihy; electronic books